Synthesis, characterization, and thermal behavior of amidosulfonates of transition metals in air and nitrogen atmosphere - Luiz, Jose Marques; Nunes, Ronaldo Spezia (Eclética Química, 2020)
The amidosulfonates of Mn2+, Co2+, Ni2+, Cu2+ and Zn2+ were prepared by the direct reaction between the metal carbonate and the amidosulfonic acid with heating and stirring. The compounds were characterized by infrared absorption spectroscopy (IRFT), elemental analysis, thermal analysis (TG and DTA) and X-ray diffraction by the powder method. The absorptions observed in IR spectra are associated with N-H and O-H stretching, as well as symmetrical and asymmetric S-O stretching in the sulfonic group. The compounds present X-ray diffraction pattern with well-defined reflections, showing no evidence of isomorphism. The TG-DTA curves allowed to establish the stoichiometry of compounds as M(NH2SO3)2.xH2O, where M = Mn2+, Co2+, Ni2+, Cu2+ and Zn2+ and x ranging from 1 to 4. Dehydration leads to the formation of stable anhydrous. In all cases the respective sulfates are formed as an intermediate. After consecutive steps of decomposition, the respective oxides were obtained: Mn3O4, CoO, NiO, CuO and ZnO. The TG-DTA curves are characteristic for each sample, with thermal events related to dehydration and ligand decomposition.